Efeito do pH e dureza da água em juvenis de Rhamdia quelen infectados com Ichthyophthirius multifiliis (Fouquet, 1876) - Garcia, Luciano de Oliveira (2008)
The aim of this study was to determine the intensity of Ichthyophthirius multifiliis infection, as well as net ion fluxes (Na+, K+ and Cl-), in silver catfish juveniles exposed to different pHs (5, 6, 7, 8, and 9 for sixteen days), pH (5.0 and 7.0) and hardness (20, 60 and 120 mg CaCO3.L-1 for sixteen days) and the oxidative stress parameters in liver, gill and muscle of this species and submitted to different pH (5.0 and 7.0 for three days). Net Na+, K+, and Cl- fluxes were determined at different times, trophonts in the skin and gill were counted, and mortality was registered daily. After six days fish kept at pH 6.0, 7.0, 8.0 and 9.0-hardness 20 mg CaCO3.L-1 showed significantly higher cumulative mortality (100% after eight days) and number of trophonts on the skin and gill compared to pH 5.0-hardness 20 mg CaCO3.L-1. Infected silver catfish showed significantly higher Na+ and K+ effluxes in the first day, and there was a recovery (influx) after the second day compared to asymptomatic juveniles. Silver catfish juveniles infected with I.multifiliis and exposed to pHs 5.0 and 7.0 presented significantly higher TBARS levels in the liver and gills compared to asymptomatic juveniles. The activity of catalase in the liver of silver catfish juveniles infected and exposed to both pHs was significantly lower (1st and 3rd day) than in asymptomatic juveniles. The GST activity in the liver and gills of infected juveniles increased throughout all experimental period compared to asymptomatic juveniles. The muscle of infected juveniles maintained at pH 5.0 showed significantly lower TBARS levels at day three compared to asymptomatic juveniles. The CAT activity was significantly lower in the muscle of infected juveniles at pH 5.0 and 7.0 at all experimental days except day 1 at pH 7.0 compared to asymptomatic juveniles. The muscle of infected juveniles presented significantly lower GST activity in all experimental period at both pH 5.0 and 7.0 compared to asymptomatic juveniles. These results allowed us to conclude that infection by I. multifiliis is less severe in silver catfish maintained at pH 5.0-hardness 20 mg CaCO3.L-1. Increase of water hardness increases trophonts infection and impairs survival in silver catfish kept at pH 5.0, but the opposite is observed when juveniles are at pH 7.0. There was no clear evidence of a relationship between mortality and trophonts number in infected silver catfish with net ion fluxes. Infection with I. multifiliis induces liver and gill damage via lipid peroxidation products, but the same is not observed in the muscle.